The Use of Infrared Thermal Imaging to Determine Functional Nasal Adequacy: A Pilot Study - Sydney Jiang MD; Jason Chan MD; Howard D. Stupak MD (OTO Open, 2021)
Objective The goal of this study was to establish a numeric threshold to separate functional from substantially obstructed noses using comparisons of thermal imaging and subjective scores. Study Design An inexpensive smartphone application and hardware attachment that uses infrared thermal imaging was tested to differentiate between substantial nasal blockage from an adequately functioning nose. Setting Sequential adult participants who presented to a public hospital otolaryngology clinic between June and August 2018 were asked to complete the Nasal Obstruction Symptom Evaluation (NOSE) tool. Methods A thermal video imaging device was used to record the difference in temperature (ΔT) between inspired (I) and expired (E) air at each nostril. The nostril ΔT between I and E air of patients with severe obstruction by the subjective measure (NOSE score) was compared with that of patients with minimal symptoms. Results A total of 26 participants were enrolled in the study. During normal respiration, Total ΔT for the nonobstructed group had a mean of 9.0, whereas the Total ΔT for the obstructed group had a mean of 7.69, a 17% difference that was statistically significant at P = .045. For the worst-performing nostril tested, ΔT for the nonobstructed group had a mean/median of 4°C, while the obstructed group had a mean of 3.23°C (median 3; 23.8% difference, P = .023). Conclusion Measures of thermal imaging, particularly at the threshold between the median scores of the worst-performing nostril, may be a useful clinical test to differentiate between a substantially obstructed nose from an adequately functioning nose, although more data are required.